2014
DOI: 10.1111/nph.12903
|View full text |Cite
|
Sign up to set email alerts
|

PSI Mehler reaction is the main alternative photosynthetic electron pathway in Symbiodinium sp., symbiotic dinoflagellates of cnidarians

Abstract: SummaryPhotosynthetic organisms have developed various photoprotective mechanisms to cope with exposure to high light intensities. In photosynthetic dinoflagellates that live in symbiosis with cnidarians, the nature and relative amplitude of these regulatory mechanisms are a matter of debate. In our study, the amplitude of photosynthetic alternative electron flows (AEF) to oxygen (chlororespiration, Mehler reaction), the mitochondrial respiration and the Photosystem I (PSI) cyclic electron flow were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
119
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(138 citation statements)
references
References 74 publications
(111 reference statements)
7
119
2
1
Order By: Relevance
“…Figures 2, 4). The fact that the steady-state P700 + level drops even in the presence of DCMU (when linear electron flow is blocked) indicates that alternative electron transport pathways might have been initiated under heat stress, the existence of which has been shown in Symbiodinium (Reynolds et al, 2008;Roberty et al, 2014;Aihara et al, 2016). The diminished response of steady-state P700 + under heat stress, when DCMU was applied might be due to the disturbance of the redox poise of P700 by DCMU (Fan et al, 2016a).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Figures 2, 4). The fact that the steady-state P700 + level drops even in the presence of DCMU (when linear electron flow is blocked) indicates that alternative electron transport pathways might have been initiated under heat stress, the existence of which has been shown in Symbiodinium (Reynolds et al, 2008;Roberty et al, 2014;Aihara et al, 2016). The diminished response of steady-state P700 + under heat stress, when DCMU was applied might be due to the disturbance of the redox poise of P700 by DCMU (Fan et al, 2016a).…”
Section: Discussionmentioning
confidence: 97%
“…Under these circumstances, as indicated here, there may be side effects on cyclic electron transport and the Mehler-AscorbatePeroxidase (MAP) pathway. Recent works (Reynolds et al, 2008;Roberty et al, 2014;Aihara et al, 2016) have indicated the possibility that singlet oxygen production is generated when PQ pool is reduced, i.e., the relative size of oxidized PQ pool is smaller (and thus charge recombination in PSII reaction centers is promoted), which may be a primary factor in coral bleaching (Vass, 2012;Rehman et al, 2016). Nevertheless, these effects have to be documented individually in corals, where it is known that there are varied responses to similar acute thermal stress scenarios (Downs et al, 2013;Gardner et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, the causes for the reduced growth rates under the two light levels are likely to be very different. A supply of excess light may require an increased investment in several forms of photoprotection, for example in the synthesis of mycosporine-like amino acids (Shick, 2004;Starcevic et al, 2010), antioxidant defense (Lesser and Shick, 1990), or alternative electron transport pathways such as the Mehler reaction (Roberty et al, 2014). Energy may also be invested in repair processes of the photosynthetic apparatus of the symbionts due to photoinhibition and subsequent damage to the D1 protein (Aro et al, 1993;Warner et al, 1999;Gorbunov et al, 2001;Hill and Takahashi, 2014), although it has been suggested that photoinhibiton may protect against oxidative damage caused by excess light (Adams et al, 2008).…”
Section: Discussionmentioning
confidence: 99%